?LIGAND EFFECT ON OXIDATION RATES OF CYSTEINE BY IRON (III) COMPLEXES - Halim, Hamzeb M Abdel-; Salama, Salama B; Burtamani, Suad K Al- (Biological Sciences - PJSIR, 1998)
Kinetics of oxidation of cysteine by iron(III). complexes of urea, CP/’ Hp,-NCS-, CN-, acac, phen, and EDTA were studied by stopped-flow spectrophotometry. Kinetic measurements were done at constant ionic strength in aqueous solutions at 25°C. Reaction rates were measured spectrophotometrically by following the change in the oxidizing agent concentration under pseudo-first order conditions in which theconcentration of cysteine was between one and two orders of magnitudes greater than that of theiron (III) complex. The results showed that the observed rate of the redox reaction depended inversely on both the strengthof the ligand in the iron (III)complex and its size.